TEACHER’S ABILITIES OF TRANSLATION OF SYMBOLIC REPRESENTATION TO VISUAL REPRESENTATION AND VICE VERSA: ADDITION OF INTEGERS - Hapizah Hapizah; Ely Susanti; Puji Astuti (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2019)
Translation of representations is a process of changing representations from one into another one. In generally, mathematics representations consists of symbolical, visual (graphical), verbal, and tabular representations. This article discusses results of research about teacher’s understanding of mathematics representations and its implementation, which is teacher’s ability of translating from symbolical representation to graphical representation and vice versa. The sample of research were 91 mathematics teacher from some districts of South Sumatera and Bangka Belitung provinces. The data of research were collected by test related to addition of integers. The results show that teacher’s ability of translating from symbolical representation into graphical representation is very low which is only 48,4% of the sample could translate the representations correctly, meanwhile teacher’s ability of translating from graphical representation into symbolical representation is quite good which is 75,8% of the sample could translate the representations correctly. The mistakes identified when the mathematics teachers translated symbolic representation to visual representation are the result of addition not presented in numbers line, no the result of addition presented at all, the order of numbers line not presented clearly, misdirection or no direction of numbers line, and no answers at all. Meanwhile the mistakes identified when the mathematics teachers translated visual representation to symbolic representation are no the result of addition presented, incorrectly order of numbers added, and no answers at all.